Cases on healthcare information technology for patient care management - Sarnikar, Surendra, 1977- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book highlights the importance of understanding the potential challenges and lessons learned from past technology implementations of health information technologies"--Provided by publisher.